Issues Related to the Use of Healthcare Communication Robots in Healthcare Settings - Yasuhara, Yuko (MALATA SAINS INDONESIA, 2025)
Introduction: Healthcare communication robots are being introduced in hospitals and nursing homes in Japan. To facilitate their implementation in such settings, it is essential to explore healthcare communication robots-related issues. Objective: This study aimed to evaluate the utilization of healthcare communication robots and identify issues related to their use immediately after introduction and 2 years later. Methods: In August 2022, focus group interviews were conducted with 11 healthcare providers (seven nurses, two occupational therapists and two care workers) at a cooperating facility for 1 h to discuss concerns related to the use of healthcare communication robots immediately after their introduction and 2 years later. The interviews were recorded using an IC recorder, transcribed, and analyzed. Results: Immediately after the introduction of Pepper a humanoid robot that supports users’ daily lives by providing recreation and conversation medical staff, particularly those responsible for managing Pepper, reported finding it “difficult to operate Pepper” and feeling “confused by the unfamiliar tasks.” Two years later, the medical staff recognized the benefits of Pepper’s use in recreational activities. Furthermore, patients at the facility looked forward to these activities. Conclusion: Although positive outcomes were observed, several challenges remained, including “Pepper’s inadequate interactive communication,” “hesitancy to handle the expensive and heavy Pepper,” “safety concerns,” and “periodic updates and malfunctions.”